Intergrown niobian rutile phases with Sc- and W-rich ferrocolumbite: An electron-microprobe and Rietveld study - Hock, Rainer; et al. (American Mineralogist, 2003)
A pegmatite from Diethensdorf, Saxonian Granulite Massif, Germany, contains fine-grained aggregates of at least three different varieties of niobian rutile and a (W, Sc)-rich ferrocolumbite. In addition, rutile I occurs as larger grains. Electron microprobe analyses of niobian rutile gave compositions close to the general formula (Fe,Mn)(x)(Nb,Ta)(2x)Ti3-3xO6 with Nb and Fe contents decreasing in the order rutile I –> rutile 2 –> rutile 3 and Ti increasing accordingly. The substitution of (Ti,Sn) by Fe + (Nb,Ta) is 35-32 at% in rutile 1, 28-26 at% in rutile 2, and 24-19 at% in rutile 3. The intergrown ferrocolumbite has Ta/(Nb + Ta) ratios of <0.10 and Mn/(Fe + Mn) ratios <0.25, and shows unusually high contents Of Sc2O3 and WO3 (UP to 4.0 and 8.8 wt%, respectively). Powder Xray diffraction (XRD) analysis with Guinier and Bragg-Brentano methods identified at least three rutile phases (herein termed A, 13, and C) with cell volumes decreasing with the Nb (+ Ta, W) contents. Nb/Ti ratios of rutiles estimated from Rietveld refinements roughly conform to the results of electron microprobe analysis. The cation distribution in the ferrocolumbite was refined on the basis of a two-scatterer model at sites 8d and 4c in space group Pbcn, leading to ordering of the heavy atoms on site 8d. Textural evidence suggests that the fine-grained intergrowths of ferrocolumbite + rutile 2 + rutile 3 (+ rutile 1) were formed by exsolution from a precursor phase that most probably was not rutile 1.